(untitled) (Research, Society and Development, 2023)
The investigation into the neurological and psychiatric manifestations of the new coronavirus (COVID-19), identified in Wuhan, China, in 2019. In addition to lung damage, the virus demonstrates the ability to affect other tissues and systems, including the nervous system, becoming lethal due to respiratory failure. The psychiatric disorders associated with the disease also demand attention due to the global emotional impact. The study aims to describe the main neurological and psychiatric manifestations in people infected during the 2020-2022 pandemic. Conducted as a narrative review, 26 scientific articles in Portuguese and English were analyzed from databases such as LILACS, MEDLINE, Portal de Periódicos da CAPES and SCIELO, published between 2019-2021. The findings included anosmia, ageusia, altered mental state and headache. The studies also addressed mental health, highlighting depression, anxiety and post-traumatic stress as the main psychiatric manifestations. The virus is believed to reach the nervous system via receptors such as ACE 2, NRP-1 and BSG/CD147. Severe patients have a high concentration of pro-inflammatory mediators due to excessive activation of the NF-kB complex. The wide range of symptoms highlights the need for in-depth studies to guide more effective therapeutic approaches to the various neurological and psychiatric manifestations associated with COVID-19.